Synthesis, α-glucosidase and β-glucuronidase inhibitory activities of bisindolylmethane bearing hydrazide-hydrazone, sulfonohydrazide and carbothioamide moieties / Obaidurahman Abid - Abid, Obaidurahman (2019)
Extensive research has been carried out on bisindole compounds due to their potent activities. Modifying the structures of bisindoles has been proven to be useful in the search for new therapeutic agents. Since varying substituents is a common method for drug design in medicinal chemistry, 66 derivatives of bisindolylmethane bearing hydrazide-hydrazone, sulfonylhydrazide, and carbothioamide moieties were synthesized and evaluated for their β-glucuronidase and α-glucosidase inhibition potential. As the first step, acid-catalyzed reaction of 5-bromo and 5-cyano, substituted indole with methyl 4-formylbenzoate was carried out. The products were reacted with hydrazine hydrate forming two key-intermediates which were further derivatized into three series of target compounds (37-102). Synthesized compounds were characterized using 1H-NMR, 13C-NMR, FT-IR, and EI-MS spectroscopic techniques. Bisindolylmethanehydrazide-hydrazone derivatives 37-66 were evaluated for their in- vitro β-glucuronidase inhibition potential while the sulfonohydrazides 67-83 and carbothioamide analogs 84-102 were tested for α-glucosidase inhibitory activity. The results are stated as IC50 values and the structure-activity relationships were established based on the presence and location of different substituents, i.e., hydroxyl, methyl, methoxy, nitro, cyano, bromine, chlorine, and fluorine. Among the bisindolylmethanehydrazide-hydrazone derivatives, trihydroxylated compounds such as 6 (0.60 µM), 20 (1.50 µM), and 25 (0.50 µM) were found to be the most active. Comparing the IC50 values, compound 25 was approximately 100 times more active than the standard D-saccharic acid 1,4-lactone (IC50 = 48.40 µM). The results from SAR reveal that the presence of hydroxyl, fluorine, and chlorine groups significantly contributes to the activity, while methyl and methoxy substituents, or replacing the benzene ring with pyridine diminishes the activity.